Ideology, capitalism, and climate: Explaining public views about climate change in the United States. (November 2016) - McCright, Aaron M.; Marquart-Pyatt, Sandra T.; Shwom, Rachael L.; Brechin, Steven R.; Allen, Summer
Abstract: Over the last three decades, climate change has become publicly defined as an important social problem deserving action. A substantial body of social science research examines the patterns of climate change views in the general publics of countries around the world. In this review essay, we identify the strongest and most consistent predictors of key dimensions of climate change views within many countries, and we also discuss the prevailing theoretical explanations of these specific effects. Since the US has yet to adopt comprehensive climate change mitigation policy and has historically played an obstructionist role in international climate negotiations, we further explain the political dynamics of US climate change views that help characterize the US's outlier status among industrial capitalist democracies. We then present an integrative theoretical framework—based upon an extension of the anti-reflexivity thesis—that explains why the strength and consistency of predictors relate to how closely those predictors distinguish ideological and material positions defending the industrial capitalist system from those positions accepting that it should be reformed or restructured. We end with a brief discussion of promising avenues through which future research may address key gaps in our understanding of climate change views.